THE PRAXEOLOGICAL-EPISTEMOLOGICAL SIGNIFICANCE OF THE ECOAESTHETIC WORLDVIEW - Teacher Niyazov Sobirjon Sodikovich (Western European Studies, 2024)
In the article, In determining the map of the ecological landscape of the world, the characteristics of reality, the eco-aesthetic thinking, the aesthetic attitude to nature is the main criterion and indicator for the history of development and its periods. In addition, it includes the possibilities of ecological consciousness and culture to form an aesthetic attitude to nature, the methods and means of its expression.
Keywords: Ecological activity; eco-aesthetic values; praxeological and epistemological